IMPLEMENTASI PERATURAN KOMISI INFORMASI NO 1 TAHUN 2021 TENTANG STANDAR LAYANAN INFORMASI PUBLIK DI PPID KABUPATEN SUMEDANG - Tiffani Adinda; Arip Rahman Sudrajat; Anne Friday Safaria (LPPM UNSAP & FISIP UNSAP, 2023)
Sumedang Regency has been ranked 4th in West Java in the informative category in the implementation of the Law No. 14 of 2008 on Public Information Disclosure (KIP). This shows that the Sumedang Regency government has been making efforts to fulfill its obligations as stipulated in the KIP Law. However, many Sumedang Regency residents are still unaware of their right to obtain public information. This is shown by the small number of residents who submitted public information requests to the Sumedang Regency PPID. In 2021, there were no public information requests from residents to the Sumedang Regency Main PPID. Meanwhile, in 2022, the number of PPID public information service visits was 16 people, consisting of students, civil servants, entrepreneurs, and others. The lack of awareness of the public's right to obtain public information shows that the public still has a poor understanding of their rights. This can hinder the government's efforts to realize public information disclosure. With the existence of PPID, the public can actively participate in government administration. This study aims to determine the implementation of the Information Commission Regulation Number 1 of 2021 on Public Information Service Standards at the Sumedang Regency PPID. This study uses a qualitative research method with a case study type. The approach used is a descriptive approach. The data collection techniques used are in-depth interviews with key informants, namely representatives of the Sumedang Regency PPID, the community, and academics. The data analysis techniques used are data reduction, data presentation, and drawing conclusions.